Synthesis of 5,7-Diamino[1,2,4]triazolo[1,2-a][1,3,5]triazines via Annulation of 1,3,5-Triazine Ring onto 3(5)-Amino-1,2,4-trizoles - Dolzhenko, Anton; Dolzhenko, A.; Chui, W. (The Japan Institute of Heterocyclic Chemistry, 2007)
The 5,7-diamino[1,2,4]triazolo[1,5-a][1,3,5]triazines were synthesized by cyclocondensation of 3(5)-amino-1,2,4-triazoles with cyanoguanidine. The substituted 3(5)-amino-1,2,4-triazoles were prepared from corresponding hydrazides and S-methylisothiourea via ring closure of the intermediate acylaminoguanidines. The 3,5-diamino-1,2,4-triazoles were prepared using partial aminolysis of dimethyl N-cyanodithiocarbonimidate followed by cyclization of the obtained N-substituted N’-cyano-S-methylisothioureas with hydrazine. The structures of the prepared compound were confirmed using NMR spectral data.